The Relationship Between Participant Satisfaction, Perceived Service Quality, and Expenditures in A Sports Event (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
This research aimed to propose a model for the enhancement of service quality of the 2nd Thailand Open Master Games 2022 in Thailand. Data were collected from a sample survey of 583 participants i.e., athletes, referees, coaches, officials, team managers, volunteers, and all involved. A simple sampling was used. A particular focus of the study is if and how participant satisfaction influences participant’ expenditures. It is hypothesized and argued that expenditure depends on satisfaction relative to perceived service quality. Descriptive and regression analytical techniques were employed for data analysis. Three primary dimensions in service quality were identified in the sports context: sporting event quality, staff quality, and venue and sports facilities quality. It is empirically found that perceived service quality affected participants' satisfaction and those participants with satisfaction greater than their perceived service quality during the visit spend significantly more. The management in sports events could apply the findings in delivering services with a view to boosting customers. A limitation of this study, however, is that the satisfaction is not measured systematically taking into consideration several dimensions of satisfaction that should be addressed in future research.